FORMULATION AND EVALUATION OF GASTRO-RETENTIVE DRUG DELIVERY SYSTEM OF NOVEL FAMOTIDINE PHOSPHOLIPID COMPLEX (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Famotidine is an H2 receptor antagonist belonging to the BCS Class II, characterized by low solubility and limited oral bioavailability. The current study encompasses the formulation of novel Famotidine phospholipid complex (FHC) with the aid of design of experiments (Central Composite Design) using solvent evaporation technique to overcome the disadvantages of Famotidine. To further enhance the physicochemical properties of FHC, it was incorporated into gastro-retentive floating tablets (GRDDS) using direct compression technique with sodium bicarbonate as a gas generating agent and its properties were compared to Famotidine floating tablets. The pre-compression parameters namely bulk density, tapped density, Hausner’s ratio, Carr’s compressibility index and angle of repose were evaluated and the flow properties of FHC granules were found to be better than the plain Famotidine granules. The post compression parameters namely thickness, hardness, friability, weight variation, drug content and swelling index showed better results for FHC as compared to Famotidine floating tablets. In vitro buoyancy study indicated that the floating lag time for FHC tablets (110±0.021 seconds) was higher than Famotidine tablets (36±0.033 seconds) owing to the higher molecular weight of phosphatidylcholine. But the total floating time for FHC tablets was found to be more than 18 hours and for Famotidine tablets it was ~12 hours indicating the improved residence time and buoyancy. The in vitro dissolution study depicted that the cumulative release for FHC tablets (99.84±0.058%) was enhanced 1.07 fold than Famotidine tablets (92.73±0.028%) and 1.6 fold than marketed tablet, Famocid (62.24±0.023%). When kinetic modelling was performed, Famotidine tablet followed zero order kinetics whereas FHC tablet followed Higuchi model indicating a modified and sustained release pattern. The statistical analysis for % cumulative release performed using ANOVA and Dunnett’s test showed the p value to be below 0.05 (0.0043) indicating that the analysis model was significant. An accelerated stability study was performed for a period of 6 months at 25±2°C; 60±5% RH. FHC tablets showed a better stability profile than Famotidine tablets. In conclusion, FHC gastro-retentive floating tablets showed improved flow properties, post compression properties, better drug content, improved in vitro buoyancy and enhanced cumulative release and stability profile.